Nilai Proksimat dan Profil Asam Amino Ikan Sembilang (Paraplotosus albilabris) dari Perairan Bintan, Kepulauan Riau - Iswandi Iswandi; Yulia Oktavia; Made Suhandana; Aidil Fadli Ilhamdy (Universitas Sriwijaya, 2021)
Eeltail catfish (Paraplotosus albilabris) is a type of marine fish that has high nutritional content but is still rarely used further. In this study, we examined the proximate content and types of amino acids found in the flesh and skin of eeltail fish (Paraplotosus albilabris). The method used in this research is measurment of morphometric, proximate content and amino acids contained in flesh and skin of eeltail catfish The result of this study showed flesh contained 16.98% protein, 1.36% ash, 79.95% water, 1.12% fat, and 0.59% carbohydrates, respectively. On the skin, there was 33.49% protein, 1.41% ash, 64.26% water, 0.36% fat, and 0.48% carbohydrates. Meat had an essential amino acid yield of 84,222.14 mg/kg (52.97%) and skin had 76,429 mg/kg (30.45%), The amount of non-essential amino acids was 74,795.7 mg/kg (47.03%), and the amount of skin was 174.669 mg/kg (69.57%).